Association Between Anxiety And Labor PainIntensity During The First Stage Of Active Labor in Primigravidas - Novi Danisia Ekayanti; Nurlailis Saadah; Astuti Setiyani; Budi Joko Santosa (International Journal of Advanced Health Science and Technology, 2025)
Maternal anxiety during childbirth is widely recognized as a psychological factor that may intensify perceivedpain and affect labor progress; however, its specific association with pain levels in primigravidas during the first active stage of labor remains under-investigated, particularly in Indonesian clinical settings. This study aimed to examine the correlation between maternal anxiety and labor pain intensity among primigravida women in the active phase of first-stage labor. An analytical observational approach with a cross-sectional design was employed. A sample of 37 primigravidas was recruited using simple random sampling at RSUD Dr. Sayidiman Magetan. Anxiety levels were measured using the Pregnancy-Related Anxiety Questionnaire-Revised (PRAQ-R2), and labor pain intensity was assessed using the Numerical Rating Scale (NRS). Data were analyzed using the Spearman Rank correlation test with a significance threshold of p < 0.05. The findings showed that the majority of respondents experienced severe anxiety, and all reported severe labor pain. Statistical testing demonstrated a moderate positive correlation between maternal anxiety and pain intensity (rho = 0.48; p = 0.002), indicating that higher anxiety was associated with heightened pain perception. In conclusion, maternal anxiety is significantly associated with increased labor pain during the first active stage in primigravidas, suggesting that psychological distress may amplify physiological pain responses during childbirth. These results highlight the importance of integrating psychological assessment and supportive interventions such as antenatal counseling, breathing regulation, structured emotional support, and relaxation techniques into maternity care practices. Future research should incorporate larger and more diverse cohorts, additional psychosocial determinants, and interventional analyses to further elucidate causal mechanisms and improve labor management strategies.